Духовне життя українців-галичан часів ІІ Речі Посполитої - Коростіль, Н. (Схід, 2009)
У статті висвітлюється суспільно-політичне становище в Західній Україні міжвоєнного періоду, дається оцінка тогочасним українським релігійним течіям, які проявлялися, з одно-
го боку, у подальшому розмежуванні сил, а з іншого, – у їх консолідації на ґрунті духовності за допомогою Греко-католицької церкви. Протистояння полонізації та асиміляції викристалізовувало в менталітеті українців-галичан духовність, яка згуртовувала мільйонні селянські
маси. The article analyses social and political life in Western Ukraine within the inter-war period. Ukrainian religious
movements of the period are being evaluated. The author concludes that on the one hand those movements resulted
in separation of forces, but on the other hand they caused consolidation of efforts on the basis of Greek Catholic
religious principles. The opposition of expansion and assimilation have molded spiritual basis of the Galician Ukrainian
mentality that have joined millions of rural citizens together.